Motivating the need for an engineering‐specific approach to student leadership development. Issue 173 (27th April 2022) - Kendall, Meagan R.; Chachra, Debbie; Gipson, Kyle; Roach, Kate
Abstract: This article illustrates the need for an engineering‐specific approach to student leadership development by exploring two contrasting case studies and the unique issues inherent to leading as engineers.